Thermo charged: the heat-powered holder / Fayeed Naufal Mansor ... [et. al] - Ahmad Ibrahim, Muhammad Ashraf; Mansor, Fayeed Naufal; Mohd Ramli, Mohamad Ridzuan; Hamdan, Muhammad Danish Iman (2024)
This abstract introduces a novel product concept—a mug holder designed to harness thermal energy from hot beverages for charging electronic devices such as smartphones. The device integrates thermoelectric generators (TEGs) and a thermal storage unit to efficiently convert heat energy into electrical power. Key design considerations include material selection for optimal heat retention and conductivity, alongside safety features to mitigate potential hazards associated with handling hot liquids. The proposed device aims to provide practical utility in both home and office environments, offering a sustainable and convenient solution for maintaining beverage temperature while simultaneously powering essential electronics. Further development focuses on enhancing energy conversion efficiency, compactness, and user-friendly design to meet diverse consumer needs and preferences.